2005
DOI: 10.1002/adma.200500858
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Cell Adhesion Using Surface‐Grafted Polymer Gradient Assemblies

Abstract: dominant bandgap emission at 310 nm, along with several higher-energy emissions due to impurity phases.In conclusion, well-defined [ZnSe](DETA) 0.5 nanobelts have been synthesized successfully by tuning the composition of a ternary solution made of DETA, hydrazine hydrate, and deionized water. We find that an appropriate amount of hydrazine hydrate is essential for the formation of elegant [ZnSe](DETA) 0.5 nanobelts. While the optical properties of the nanobelts are not changed significantly, the ability to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
146
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(147 citation statements)
references
References 38 publications
1
146
0
Order By: Relevance
“…Spatial regulation of cell-material interactions has led to myriad new applications and fundamental insights into cell growth, [4,5] differentiation, [6] and adhesion. [7,8] However, until recent developments in dynamic regulation of cell-material interactions, [9,10] patterned cells were trapped within the confines of the adhesive islands and only the first step of cell migration-lamellipodia extensioncould be investigated. [11,12] Moreover, the cell-resistant regions that define the patterns preclude the formation of confluent cell layers desirable for engineering tissues.…”
mentioning
confidence: 99%
“…Spatial regulation of cell-material interactions has led to myriad new applications and fundamental insights into cell growth, [4,5] differentiation, [6] and adhesion. [7,8] However, until recent developments in dynamic regulation of cell-material interactions, [9,10] patterned cells were trapped within the confines of the adhesive islands and only the first step of cell migration-lamellipodia extensioncould be investigated. [11,12] Moreover, the cell-resistant regions that define the patterns preclude the formation of confluent cell layers desirable for engineering tissues.…”
mentioning
confidence: 99%
“…[14][15][16] Although membrane fouling is a very complicated process, many investigations have shown that an increment in membrane hydrophilicity will inevitably inhibit protein adsorption and deposition, thereby significantly reducing membrane fouling. [17][18][19] Therefore, the ionic modification was applied with the aid of dual-layer hollow fiber technology in this work to tune the pore size and pore size distribution, introduce the electrostatic interaction, and reduce membrane fouling for longterm high-performance protein separation. Polyethersulfone (PES) was chosen as the polymer material and two kinds of ionic modification approaches (i.e., sulfonation and triethylamination) were used in the PES membrane.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Such gradient techniques provide a fast and convenient tool for combinatorial screening of polymeric surfaces over a spectrum of material parameters. [33][34][35] PHEMA was chosen because it is a well-established biomaterial that can resist nonspecific protein adsorption and cell adhesion, 36 and also because it is amenable to the ATRP technique used to create the gradients.…”
Section: Introductionmentioning
confidence: 99%